2020
DOI: 10.1371/journal.pone.0227024
|View full text |Cite
|
Sign up to set email alerts
|

Designing information provision to serve as a reminder of altruistic benefits: A case study of the risks of air pollution caused by industrialization

Abstract: A well-known phenomenon is that humans perceive risks to threaten future generations as more dangerous in many cases. However, this tendency could be changed depending on certain conditions and could potentially be explained by the evolution of altruism. Our multiagent simulation model, which was constructed to identify attributes contributing to subjective assessment of a risk source based on kin selection theory, showed that support from relatives can affect the agents' subjective risk assessment. We utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
21
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(37 citation statements)
references
References 17 publications
(14 reference statements)
11
21
5
Order By: Relevance
“…The differences were especially small in T2 for Future Generations, which is our main target for interventions, and in T1 for Future Generations. The trend in the previous study for air pollution caused by industrialization was that younger respondents showed larger D than older respondents [27] (S2 Appendix in S1 File), which was the opposite of that in the present study.…”
Section: Plos Onecontrasting
confidence: 99%
See 4 more Smart Citations
“…The differences were especially small in T2 for Future Generations, which is our main target for interventions, and in T1 for Future Generations. The trend in the previous study for air pollution caused by industrialization was that younger respondents showed larger D than older respondents [27] (S2 Appendix in S1 File), which was the opposite of that in the present study.…”
Section: Plos Onecontrasting
confidence: 99%
“…In the previous study for air pollution caused by industrialization, the sex differences in D were not observed in Canada (S2 Appendix in S1 File), whereas the present study showed clear sex differences. Thus, our designed messages, at least for disposable plastics, had a stronger effect for increasing positive attitudes of women than men in all three countries, different from our previous nudging messages for air pollution caused by industrialization [27] (S2 Appendix in S1 File).…”
Section: Plos Onecontrasting
confidence: 86%
See 3 more Smart Citations